Dr. R. K. Gadgil - An eminent Indian pathologist, pioneer in starting rural medical camps and a researcher who discovered an endemic focus of schistosomiasis in Maharashtra, India - Dhaneshwar N Lanjewar; Ulhas L Wagholikar; Vijay V Joshi (Wolters Kluwer Medknow Publications, 2020)
Dr. Ramchandra Krishnaji Gadgil (RKG) was a pioneer and an eminent researcher. Along with clinician colleagues, he started rural medical camps in 1952, in Maharashtra, India. Through his meticulous research, he discovered in the same year an endemic focus of schistosomiasis in the village, Gimvi, and in 1956, went on to establish a life cycle of the Schistosoma hematobium, involving a completely new intermediate Mollusk host "Ferrisia tenuis", a rather epoch making discovery in the realm of Mollusk intermediate host in relation to human schistosomiasis. His instructions and guidance to the Government Public Health department led eventually to eradication of the schistosomiasis focus in that village in 1969, thereby setting an example for pathologists to head out into the field, do clinical work and pursue with disciplined curiosity a new pathological finding in the laboratory. The fascinating story of his life, education and research is described in this paper.